A Novel DAL Scheme With Shared-Locking for Semantic Conflict Prevention in Unconstrained Real-Time Collaborative Programming - Fan, Hongfei (2017)
Real-time collaborative programming allows a team of programmers to concurrently edit the shared source code document at the same time. To support semantic conflict prevention in real-time collaborative programming, a dependency-based automatic locking (DAL) approach was proposed in prior work, which automatically grants locks on source code regions with dependency relationships. The prior DAL scheme was devised under two assumptions that are not realistic, and together with other restrictions, they become serious problems in applying the DAL approach and techniques in real-world programming scenarios. To address the issues under the prior DAL scheme, this paper presents a novel DAL scheme with a shared-locking approach, which ensures the responsiveness, effectiveness, and consistency of semantic conflict prevention in unconstrained real-time collaborative programming. Under the novel DAL scheme, programmers can perform concurrent editing operations with overlapping locking scopes and perform editing operations that may dynamically change the source code structure, while three types of shared-locking are allowed under well-defined circumstances with reasonable design rationales. In addition, we have presented major technical issues and solutions in realizing the scheme, which has been implemented in a research prototype. Experimental evaluations have confirmed the good performance of the novel DAL scheme and its supporting techniques.